2003
DOI: 10.1159/000070925
|View full text |Cite
|
Sign up to set email alerts
|

Magnoliae Flos Induces Apoptosis of RBL-2H3 Cells via Mitochondria and Caspase

Abstract: Background: Magnoliae flores (MF), the buds of Magnolia denudata Desrousseaux, have been successfully used for the management of allergic diseases in Korea. The purpose of the present study was to determine their causal role in inducing apoptosis of mast cells and to verify the underlying mechanism. Methods: The viability of mast cells was assessed by the trypan blue exclusion test. Induction of apoptosis was confirmed by DNA fragmentation, nuclear staining and DNA hypoploidy. Western blotting and immunofluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…The plants of the Magnoliaceae have been used in Korea as a medication for a variety of diseases, including allergic rhinitis, fever, headache, anxiety, diarrhea, stroke and asthma (Wang et al, 2000;Kim et al, 2003). Magnolia kobus is a medicinal plant of the Magnoliaceae and pharmacological activities of a flower bud of Magnolia kobus are well characterized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plants of the Magnoliaceae have been used in Korea as a medication for a variety of diseases, including allergic rhinitis, fever, headache, anxiety, diarrhea, stroke and asthma (Wang et al, 2000;Kim et al, 2003). Magnolia kobus is a medicinal plant of the Magnoliaceae and pharmacological activities of a flower bud of Magnolia kobus are well characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional Oriental medicine Magnoliae Flos, a dried flower bud of Magnolia kobus, Magnolia denudata or Magnolia fargesii, has long been used for the treatment of nasal congestion with headache, sinusitis and allergic rhinitis (Jung et al, 1998;Bae, 2000;Kim et al, 2003). Recent studies also revealed that it has antirheumatic and antiangiogenic activities (Kobayashi et al, 1996(Kobayashi et al, , 1998.…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of fact, the antiinflammatory or antiallergic effect of a certain drug was demonstrated to depend on its apoptosis-inducing effect (Fuller et al, 1995;Park et al, 2001;2002;Kim et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The herbal drug has been used for managing nasal conjestion with headache, sinusitis and allergic rhinitis. [1][2] It has also a wide range of pharmacological effects including antirheumatic, 3 antiangiogenic, 4 antiallergic, [5][6][7][8] antiinflammatory, [9][10] and anitmicrobial activities.…”
Section: Introductionmentioning
confidence: 99%